Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/jgo-22-477
|View full text |Cite
|
Sign up to set email alerts
|

Rectal tumor fragmentation as a response pattern following chemoradiation

Abstract: Background: Tumor response to neoadjuvant therapy is heterogenous and prognostically important for locally advanced rectal adenocarcinoma (LARC) patients. Commonly applied response classification approaches including tumor regression grading (TRG) and TN downstaging can be discordant. The aim of this study is to compare the prognostic value of discordant tumor response measurement categorized according to the AJCC/CAP TRG schema and ypTN stage. Methods: This is a single-center retrospective review of 90 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…While some studies have suggested that T downstaging may not be associated with therapeutic efficacy or prognosis, it is important to consider the potential impact of this factor on patient outcomes [ 36 , 37 ]. Mills et al [ 38 ] found that T downstaging was not prognostically significant, while patients with TRG 3 were associated with inferior DFS; thus, they considered response categorization discrepancies may be partly explained by alternative patterns of residual disease, including tumor fragmentation. Similar to their conclusions, in the survival analysis of any group of patients, we did not find any correlation between T downstaging and OS, or DFS.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that T downstaging may not be associated with therapeutic efficacy or prognosis, it is important to consider the potential impact of this factor on patient outcomes [ 36 , 37 ]. Mills et al [ 38 ] found that T downstaging was not prognostically significant, while patients with TRG 3 were associated with inferior DFS; thus, they considered response categorization discrepancies may be partly explained by alternative patterns of residual disease, including tumor fragmentation. Similar to their conclusions, in the survival analysis of any group of patients, we did not find any correlation between T downstaging and OS, or DFS.…”
Section: Discussionmentioning
confidence: 99%